SDN control and forwarding method based on identity attribute - Xianwei ZHU; Chaowen CHANG; Zhiqiang ZHU; Xi QIN (Tongxin xuebao)
Due to the lack of effective data source authentication mechanism and the limited matching fields in software defined networking (SDN),an SDN security control and forwarding method based on identity attribute was proposed.Attribute identification and attribute signature were generated by device attributes and encapsulated in the group header.When the data flow left the network,the data was verified by the forwarding device to ensure the validity of the data flow.At the same time,attribute identification was defined as a match field of flow by the framework,and the network forwarding behavior was defined based on attributeidentification.A fine-grained access control was implemented by the proposed mechanism and attribute-based signature.The proposed mechanism and attribute-based signature implemented a fine-grained access control.Experimental results demonstrate that the method can effectively implement fine-grained forwarding and flow authentication,and the forwarding granularity is higher than that of similar schemes.